Optimal power scheduling of renewable energy sources in micro-grid via distributed energy storage system - Ibrahim Alhamrouni; Firdaus Ramli; Mohamed Salem; Bazilah Ismail; Awang Jusoh; Tole Sutikno (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
This research is mainly focusing on the optimal power management by controlling the charging and discharging modes of the battery storage of the micro-grid (MG). A droop-based controller or battery controller is proposed for this work in order to optimize the power management of the battery. Charging and discharging modes are controlled by the droop-based characteristic where it will perform as a battery controller for the battery storage. Furthermore, the charging and discharging rates will depend on the signal from the MG at power secondary and its signal will be read by the battery controller and choose either to charge or discharge the battery storage where it will suffice the energy demand by loads in the micro-grid. The simulation results show the effectiveness of the controller to control sharing the power based on the desired energy from the battery storage to the loads at the MG. Moreover, all the critical cases have been advised, such as sudden decrease or disturbance of any generating unit. The result has been observed that due to sudden decrease or disturbance of any generating unit, the battery controller manages to control the charging and discharging rate based on the insufficient energy caused by the disturbance to fulfil the demand at MG.